Menelisik Omnibus Law Bidang Perencanaan Anggaran - Suliantoro, Irwan (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2023)
In the context of budget regulations, in 2023, Government Regulation Number 6 of 2023 and Minister of Finance Regulation Number 62 of 2023 were issued which have the omnibus law character. This research aims to examine the omnibus law in the field of budget planning to analyze whether there are substances that have not been regulated, substances that are less in line with other regulations, and substances that from a grammatical perspective give rise to multiple interpretations. The research method was carried out through a descriptive qualitative approach. The research results show that the mechanism for preparing the state budget has not been fully described by the state budget cycle, the preparation of the Medium-Term Development Plan and the Medium-Term Expenditure Framework (from the funding side) needs to refer to the Medium-Term Budget Framework. In addition, the mechanism for calculating the Medium-Term Expenditure Framework has not been fully described. Furthermore, to increase the efficiency of budget allocation, it is best to add, reduce, and or shift the budget ceiling not only at the line ministries level but also need to be done at the national level. The mechanism is carried out through national blocking savings, where inefficient allocations are blocked and savings are made, then when preparing the Budget Allocation, the figures resulting from the national saving are redistributed to priority programs/activities in various line ministries.